Mechanical Ventilation Trigger Tool Identify Errors Associated with Mechanical Ventilation in Newborn Infant - ELMeneza, Safaa Abd ELHamid; Koriem, Maryam Abd ELSamee; Ibrahim, Asmaa Abd Elwakeel (Open Access Macedonian Journal of Medical Sciences, 2023)
BACKGROUND: Patient safety is the core of quality of health care. Newborn infants who are admitted to NICU are liable to adverse events. Medical errors represent a serious public health problem and pose a threat to patient safety. Mechanical ventilation is a complex procedure that exposes newborn infants to adverse events and complications. AIM: The objective of this study was to identify medical errors related to mechanical ventilation (MV) in newborn infants using the newly design MV trigger tool. METHODS: Observational cohort study was conducted for 6-month duration to determine the medical errors related to mechanical ventilation. It was carried out on newborn infants who needed mechanical ventilation and admitted to the NICU. Furthermore, we used the mechanical ventilation trigger tool to estimate number, types, and risk factors for the related errors. RESULTS: There were 142 errors related to mechanical ventilation. Nearly 21.13% of the errors were related to ventilator settings, 38.39% were related to endotracheal intubation, and 40.14% of the errors were due to manipulation of the ventilators. The adverse events were diagnosed in 73.24% of the detected errors. Error of commission was seen in 53.5% of cases, and omission errors were reported in 46.5% of the cases. Mechanical ventilation trigger tool has 95.87% sensitivity and 95.24% specificity with 95.77% accuracy to detect errors. CONCLUSION: The mechanical ventilation trigger tool may be efficient and effective in identifying errors and adverse events related to mechanical ventilation; it has high sensitivity and specificity. It might increase awareness to improve MV-related care.